2022
DOI: 10.1038/s12276-022-00765-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional and pathologic association of aminoacyl-tRNA synthetases with cancer

Abstract: Although key tumorigenic and tumor-suppressive factors have been unveiled over the last several decades, cancer remains the most life-threatening disease. Multiomic analyses of patient samples and an in-depth understanding of tumorigenic processes have rapidly revealed unexpected pathologic associations of new cellular factors previously overlooked in cancer biology. In this regard, the newly discovered activities of human aminoacyl-tRNA synthases (ARSs) deserve attention not only for their pathological signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 104 publications
(122 reference statements)
1
26
0
Order By: Relevance
“…Despite their similarity across organisms, the sequence and topological differences between pathogenic microbial AARSs and human AARSs make it possible to design drugs that selectively inhibit pathogen AARSs 3 . AARSs suppression can be exploited for cancer chemotherapy since over-proliferating cancer cells are more sensitive to AARSs suppression than normal cells 4 . For these reasons, AARS are underexploited therapeutic targets 5 .…”
mentioning
confidence: 99%
“…Despite their similarity across organisms, the sequence and topological differences between pathogenic microbial AARSs and human AARSs make it possible to design drugs that selectively inhibit pathogen AARSs 3 . AARSs suppression can be exploited for cancer chemotherapy since over-proliferating cancer cells are more sensitive to AARSs suppression than normal cells 4 . For these reasons, AARS are underexploited therapeutic targets 5 .…”
mentioning
confidence: 99%
“…Notably, nucleotide metabolism and aminoacyl-tRNA biosynthesis pathways stood out as particularly affected with many of the main genes involved in the two processes being downregulated. Aminoacyl-tRNA biosynthesis is directly involved in the progression of gastric cancer, and its targeting has been proposed as a viable treatment strategy 29,39 . Similarly, sustained and aberrant nucleotide metabolism is a critical component in cancer development as it constitutes a cancer dependency independently of cancer type, tissue of origin, or driving molecular alteration 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the continued interest in aminoacyl‐tRNA synthases (ARSs) has delivered their pathological significance in carcinogenesis and clinical implications in therapy 7,8 . ARSs as a class of catalytic enzymes transport amino acid to cognate tRNAs for cell protein synthesis 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the continued interest in aminoacyl‐tRNA synthases (ARSs) has delivered their pathological significance in carcinogenesis and clinical implications in therapy 7,8 . ARSs as a class of catalytic enzymes transport amino acid to cognate tRNAs for cell protein synthesis 7 . Research has demonstrated that ARSs severed as regulators, sensing diverse cellular conditions and influencing various cellular processes, thus establishing connections with tumorigenesis 7 .…”
Section: Introductionmentioning
confidence: 99%